Political contestation and the Second Great Divergence - John, Richard R. (History compass, 2022)
This essay considers Piketty's characterization of U.S. economic development in Capital and Ideology in the decades between 1860 and 1900, a period that historians have begun to call the “Second Great Divergence.” It contends that Piketty's characterization of this period rests on outdated assumptions about the relationship between economic development and political contestation, and that Piketty's neglect of historical writing on this topic raises questions about his policy proposals. To highlight the limitations of Piketty's approach, it includes case studies of the telegraph industry and the telephone industry. For all of its erudition, range, and literary panache, Piketty's Capital and Ideology is, at its most persuasive, an updated restatement for a twenty-first century audience of the Polanyian critique of nineteenth-century economic liberalism. This is a worthy project, yet it is less novel in its conception and more problematic in its execution than might at first appear.